Promotion of Disposable Electronic Cigarette Flavors and Topics on Twitter - Sun, Li (Int J Environ Res Public Health, 2020)
Disposable electronic cigarettes (e-cigarettes) became popular among youth after the Food and Drug Administration (FDA) implemented an enforcement policy to restrict the sale of cartridge-based flavored e-cigarettes starting from February 2020 in the United States (US). We aimed to examine the flavors and topics related to disposable e-cigarettes on Twitter. The Twitter dataset, which includes 1489 tweets, was collected by the Tweepy streamapplication programming interface (API) using a keyword query from March to September 2020. The disposable e-cigarette flavors were curated from both online stores and collected tweets. Topics related to disposable e-cigarettes on Twitter were manually coded. Distributions of topics were compared between tweets from the US and tweets from non-US countries. The temporal analysis results showed a slight increase in the number of discussions over the study period. Strawberry, mango, watermelon, and mint were the most popular flavors of disposable e-cigarettes mentioned on Twitter. Almost all the tweets (97.11%) were commercial tweets, which were dominated by topics related to the product and flavor promotions. The US tweets focused more on product and flavor promotions and less on price promotions compared to non-US tweets. Our results suggest that companies exploited the limitations of legislation to promote flavors on Twitter, which could undermine public health and young people’s finances if they get hooked on addictive products.